2011
DOI: 10.1093/forestry/cpr030
|View full text |Cite
|
Sign up to set email alerts
|

Structural dynamics and synchronous silver fir decline in mixed old-growth mountain forests in Eastern and Southeastern Europe

Abstract: Research on old-growth forests is essential for understanding forest ecosystem functioning and for the development of forest management strategies. Their structural dynamics depends on disturbance patterns (White and Pickett, 1985). In recent decades, much research in old-growth forests has focused on natural disturbances. However, over several centuries, the natural disturbance regime has been severely altered by forest fragmentation, changes in fire regime, fauna extinctions, the introduction of forest manag… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
70
0
3

Year Published

2014
2014
2021
2021

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 88 publications
(80 citation statements)
references
References 37 publications
3
70
0
3
Order By: Relevance
“…Tree species composition according to growing stock in Janj comprised one of the highest shares of conifers (84%) when compared to other old-growth forests in the region [15,44,47,60]. A similar low percentage of beech (18%) was found in the Igman old-growth forest in BiH, which is located about 92 km in the southeast direction.…”
Section: Recent Stand Structure In Janj and Comparison With Similar Omentioning
confidence: 75%
See 4 more Smart Citations
“…Tree species composition according to growing stock in Janj comprised one of the highest shares of conifers (84%) when compared to other old-growth forests in the region [15,44,47,60]. A similar low percentage of beech (18%) was found in the Igman old-growth forest in BiH, which is located about 92 km in the southeast direction.…”
Section: Recent Stand Structure In Janj and Comparison With Similar Omentioning
confidence: 75%
“…Namely, lower SO 2 emissions [36] and lower deer densities [35] may be responsible for the less pronounced silver fir decline in Bosnia. Diaci et al [15] indicated a synchronous silver fir decline in most studied southeast European mixed old-growth mountain forests, while the share of fir in BA increased in the Igman and Trstionica mixed old-growth mountain forests in Bosnia. The data from this study indicated a more pronounced spruce decline in comparison to fir, which may be attributed to its greater susceptibility to drought and high temperatures at the limit of its geographic range towards the Adriatic Sea [62], or its successional stage due to past (anthropogenic) disturbance.…”
Section: Six Decades Of Structural Changes In the Janj Lom And Perucmentioning
confidence: 96%
See 3 more Smart Citations